(3GdHMQ GdQGFb TQM cfR GdObGFbs - (3GdeUQj GdMfaj, GHf fLje, Rjf GdOjf Hf EHQGgje Hf eMeO, (B970 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; cJGH Gdhba efGSHI ddTQcI HGYJHGQ Cf GdebUhO Hcd efgeG GdGfJaGY HeG jRjO Ydi CUd GdeGd hdg eYfi dZhj hTQYj hSHH heMd hTQGFWs
(3BNQgG (B:s
(3hEf cGfJ eSeGI jfHZj Cf dG jLGhR Hg GdeSei cZjQgG ef GdTQhW bO PcQgG aj GdNdGUI hde jJYQV ddCLQI Ke bGd hEf TQW Cf jScfgG GdeSJCLQ hMOg jLhRs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 64s
(3eYLe GdeDdajf (B1 / 740s
(3cTa GdXfhf (B2 / 1515s
(3TPQGJ GdPgH (B8 / 358s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs